The Price of a Helping Hand: Modeling the Outcomes and Costs of Bystander CPR. (2nd October 2015) - Bouland, Andrew J.; Risko, Nicholas; Lawner, Benjamin J.; Seaman, Kevin G.; Godar, Cassandra M.; Levy, Matthew J.
Abstract: Objective. Early, high-quality, minimally interrupted bystander cardio-pulmonary resuscitation (BCPR) is essential for out-of-hospital cardiac arrest survival. However, rates of bystander intervention remain low in many geographic areas. Community CPR programs have been initiated to combat these low numbers by teaching compression-only CPR to laypersons. This study examined bystander CPR and the cost-effectiveness of a countywide CPR program to improve out-of-hospital cardiac arrest survival.Methods. A 2-year retrospective review of emergency medical services (EMS) run reports for adult nontraumatic cardiac arrests was performed using existing prehospital EMS quality assurance data. The incidence and success of bystander CPR to produce prehospital return of spontaneous circulation and favorable neurologic outcomes at hospital discharge were analyzed. The outcomes were paired with cost data for the jurisdiction's community CPR program to develop a cost-effectiveness model.Results. During the 23-month study period, a total of 371 nontraumatic adult out-of-hospital cardiac arrests occurred, with a 33.4% incidence of bystander CPR. Incremental cost-effectiveness analysis for the community CPR program demonstrated a total cost of $22, 539 per quality-adjusted life-year (QALY). A significantly increased proportion of those who received BCPR also had an automated external defibrillator (AED) applied. There was no correlation between witnessed arrest and performance of BCPR. A significantly increased proportion of those who received BCPR were found to be in a shockable rhythm when the initial ECG was performed. In the home setting, the chances of receiving BCPR were significantly smaller, whereas in the public setting a nearly equal number of people received and did not receive BCPR. Witnessed arrest, AED application, public location, and shockable rhythm on initial ECG were all significantly associated with positive ROSC and neurologic outcomes. A home arrest was significantly associated with worse neurologic outcome.Conclusions. Cost-effectiveness analysis demonstrates that a community CPR outreach program is a cost-effective means for saving lives when compared to other healthcare-related interventions. Bystander CPR showed a clear trend toward improving the neurologic outcome of survivors. The findings of this study indicate a need for additional research into the economic effects of bystander CPR.Key words: CPR; EMS; cost effectiveness